Managers in the making : careers, development and control in corporate Britain and Japan - Storey, John, 1947- (Industrial Management series., 1997)
Using original data, Managers in the Making presents a thorough analysis of the processes by which managers are made in Britain and Japan. It provides a detailed comparative study of the careers, training, developmental experience and job demands of managers in eight named companies, matching British firms with Japanese counterparts. Using qualitative and quantitative data the authors offer an understanding of these processes within organizational, sectoral and national contexts. Managers' perceptions, reactions and concerns are recorded and analysed throughout.